Local stability of web of tapered beam subjected to pure bending - Šapalas, Vaidotas (Journal of Civil Engineering and Management, 2010)
This paper deals with a theoretical and a numerical analysis of local stability of web of tapered beams subjected to a pure bending moment. A standard FEM code COSMOS/M has been used for a numerical estimation of a critical load multiplier. It has been assumed that the critical stress of the web of tapered beam could be calculated in an analogous way as for uniform member just with an additional correction factor αb.w. A large number of simulations carried out within a wide range of the ratios of second moments of area allowed to determine the proper values of that factor. In the paper there was investigated the influence of steel grade, relative slenderness and beam’s ends cross‐section moments of inertia ratio to the local stability of web of the tapered beam subjected to pure bending. First Published Online: 24 Jun 2011